Written Feedback for French L2 Papers - Chao Chao, Kuok Wa (2021)
In order to analyze how students use annotated comments from their instructors, the Rodet model (2000) is used as the basis of this study in order to identify the various types of corrective feedback provided. The subjects included three University of Costa Rica French instructors and their students. Data was gathered from group discussions and student paper analysis with QDA Miner. Results reveal that instructors tend to use cognitive, constructive and informational feedback. Students responded positively to such feedback and stated that it was motivational, delivered clearly and highlighted what needed to be corrected. The author suggests that instructor feedback be more descriptive, specific and immediate to maximize student benefit.